Sentinel Lymph Node Biopsy for Cutaneous Head and Neck Melanoma: Mapping the Parotid Gland - Picon, Antonio I. (Ann Surg Oncol, 2006)
BACKGROUND: Sentinel lymph node biopsy (SLNB) for primary cutaneous head and neck melanoma (CHNM) has been shown to be successful and is the current standard of care for intermediate-thickness melanoma. We evaluated our experience with CHNM associated with SLNB mapping to the region of the parotid gland. METHODS: Retrospective review of a prospectively collected melanoma database identified 1014 CHNMs. Two-hundred twenty-three patients underwent SLNB, and 72 (32%) had mapping in the region of the parotid gland between May 1995 and June 2003. RESULTS: The mean number of SLNs per patient was 2.5. A sentinel lymph node (SLN) was successfully identified in 94% of patients, and in 12%, the SLN was positive for metastatic disease. Biopsy of intraparotid SLNs was performed in 51.4% and of periparotid SLNs in 26.4%, and a superficial parotidectomy was performed in 22.2%. Ten patients were found to have lymph nodes in the parotid region with metastatic disease (eight identified by SLNB), and two (20%) patients developed intraparotid lymph node recurrence in the setting of a negative SLNB. Same-basin recurrence in SLN-negative patients was 3.3% with a median follow-up of 26 months. Facial nerve dysfunction was identified in seven (10%) patients. Facial nerve function returned to preoperative status in all patients. CONCLUSIONS: SLNB for patients with primary CHNM mapping to the parotid gland can be performed with a high degree of accuracy and a low morbidity consisting of temporary facial nerve paresis.